2021
DOI: 10.1002/jia2.25847
|View full text |Cite
|
Sign up to set email alerts
|

Size of HIV‐1 reservoir is associated with telomere shortening and immunosenescence in early‐treated European children with perinatally acquired HIV‐1

Abstract: IntroductionPersistence of HIV‐1, causing chronic immune activation, is a key determinant of premature senescence. Early antiretroviral therapy (ART) has been associated with a reduced HIV‐1 reservoir in children with perinatally acquired HIV‐1 (PHIV), but its impact on the senescence process is an open question. We investigated the association between HIV‐1 reservoir and biological and immune ageing profile in PHIV enrolled in the multicentre cross‐sectional study CARMA (Child and Adolescent Reservoir Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…While there is optimism regarding the potential of combination approaches, it is important to acknowledge that a scalable, clinically well-tolerated therapeutic strategy to either cure or control HIV in the absence of ART is unlikely to occur in the same timescale as has been proposed to end the HIV epidemic (ie, by 2030) [ 6 , 8 ]. As such, an emerging area of concern is to address how age-related perturbations in immune function and HIV-associated immunosenescence [ 162 164 ] intersect with the maintenance of infected cells during long-term ART [ 165 ], with the risk of co-morbidities [ 166 - 168 ], and with responsiveness to immune-based cure strategies [ 169 171 ]. Moreover, a portfolio of experimental and FDA-approved drugs are under investigation for their ability to either eliminate (ie, senolytics) or alter the function (ie, senomorphic) of senescent cells, including Bcl-2 inhibitors (Venetoclax), JAK1/JAK2 inhibitors (ruxolitinib), mTOR inhibitors (rapamycin), and tyrosine kinase inhibitors (dasatinib) among others [ 172 , 173 ]; however, further study is required to evaluate these agents for their utility in attenuating or reversing HIV-induced immunosenescence and affecting HIV persistence.…”
Section: Progress Towards a Curementioning
confidence: 99%
“…While there is optimism regarding the potential of combination approaches, it is important to acknowledge that a scalable, clinically well-tolerated therapeutic strategy to either cure or control HIV in the absence of ART is unlikely to occur in the same timescale as has been proposed to end the HIV epidemic (ie, by 2030) [ 6 , 8 ]. As such, an emerging area of concern is to address how age-related perturbations in immune function and HIV-associated immunosenescence [ 162 164 ] intersect with the maintenance of infected cells during long-term ART [ 165 ], with the risk of co-morbidities [ 166 - 168 ], and with responsiveness to immune-based cure strategies [ 169 171 ]. Moreover, a portfolio of experimental and FDA-approved drugs are under investigation for their ability to either eliminate (ie, senolytics) or alter the function (ie, senomorphic) of senescent cells, including Bcl-2 inhibitors (Venetoclax), JAK1/JAK2 inhibitors (ruxolitinib), mTOR inhibitors (rapamycin), and tyrosine kinase inhibitors (dasatinib) among others [ 172 , 173 ]; however, further study is required to evaluate these agents for their utility in attenuating or reversing HIV-induced immunosenescence and affecting HIV persistence.…”
Section: Progress Towards a Curementioning
confidence: 99%
“…As already mentioned, periodontitis is a chronic inflammatory disease modulated by the immune system that can be associated with a series of risk factors, similar to those shared by aging. Additionally, chronic medication use, comorbidities, immunosenescence, and alteration of the inflammatory and immune responses resulting from aging can influence the onset and progression of periodontitis [ 38 , 39 ]. In our sample, it was possible to observe a significant correlation between periodontitis and older age (OR A = 4.674).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown the influence of HIV and antiretroviral medication on accelerating the aging process in people living with HIV. The mechanisms by which HIV can influence accelerated immunosenescence in young individuals can be explained by chronic immune activation, high profile of inflammation played by B cells, replicative senescence of CD4 and CD8 T-cells, frequencies of naïve cells, and the innate immune response presented by infected individuals [ 39 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, HIV-1 persistence contributes to a premature immune-senescence [ 36 ], often exacerbated by CMV coinfection [ 37 , 38 ], and a higher susceptibility to age-associated multi-morbidity [ 39 ]. Interestingly, children with perinatally acquired HIV-1 (PHIV) also face a premature T cell senescence that could be limited by an early administration of ART, which prevents viremia explosion [ 40 , 41 ].…”
Section: The ‘Inflammaging’ Of Cd8 + T Cells Durin...mentioning
confidence: 99%